Immersive Virtual Reality in Architecture: Architect's Response During Pandemics (International Conference of Graduate School on Sustainability (ICGSS), 2020)
The covid-19 pandemic resulted in changes in the environment and all lifelines, including architecture.  In architectural design, it is important to communicate ideas effectively in visual form. Virtual practice strengthens as interaction patterns change during pandemics. The purpose of this article is to review the stages of architectural design, presentation of architectural works, virtual reality concepts, the use of virtual reality technology in architecture, the step of development work and immersive use of virtual reality technology in architectural design, and the use of virtual reality as a form of artificial environmental visualization in answering the role of architects during pandemic times. This article uses a descriptive narrative method that is the description of research or literature, by combining context based on the data collected. The conclusion obtained from this article review, that virtual reality technology is very effective in architectural design, gives the user the experience to immerse in an artificial environment with touchless principles. Keywords: architecture; immersive; pandemic; touchless; virtual reality